Explorando a curiosidade e a criatividade como motivadores do interesse em matemática - Nogueira, Jair Pinheiro (2014)
For the process of teaching and learning Mathematics it takes more than just writing the subject matter on the blackboard. The participation and creativity should be encouraged and developed. New activities with a more dynamic and creative vision of Mathematics need to be incorporated into the daily life of the student so that it increases their interest in the study of this discipline that, in most cases, is unwanted. Activities such as challenges, tricks and trivia, if well founded mathematically, can play a role in stimulating the study and learning Mathematics in a more creative and joyful manner. Every new and di erent situation tends to develop curiosity and, gradually, the creativity of the individual. Each time a student overcomes a challenge, it builds up self-con dence and self-esteem. Based on this real need, the main goal of this work is to study the e ect of the introduction of such activities in the routine of the classroom on the attitude of students toward Mathematics and its study. These activities were carried out with high school classes during the second academic semester of 2013. Each of these activities, whether challenge, trick or curiosity, besides covering some curriculum content, is well described and explained in the form of suggestions for fellow teachers. In order to improve the analysis of the e ects of the project, the students answered two questionnaires, the rst at the beginning of the semester and the second, after the end of the semester. On the analysis of responses to the questionnaire and the participation of class sizes, a change in the involvement and interest of students in math classes can be observed, and this e ect does not seem to be correlated to the degree of prior involvement of each class.